المسؤولية الجزائية عن تناول الرياضيين للمنشطات في التشريع الجزائري - بوخاري, مصطفى (جامعة الوادي - University of Eloued, 2018)
تقوم المسؤولية الجزائية للرياضي في حالة استعماله للمنشطات اثناء المسابقات الرياضية، و يتم توقيع عليه عقوبات جزائية بالإضافة الى العقوبات التأديبية؛ فهي وسيلة للمحافظة على الاعراف الرياضية عند كل احتفالية بالمسابقات حتى يسودها المساواة بين الرياضيين المشاركين فيها و ضمان عدم تدخل اي وسيلة غير اخلاقية ومحظورة دوليا تسهل التقدم على الاخرين، و لقد اكد المشرع الجزائري على جريمة تعاطي المنشطات من قبل الرياضيين و عاقب كذلك كل شخص يسهل توفير هذه المواد بهدف المشاركة في مختلف المسابقات الرياضية باستعمال جهد اضافي غير طبيعي .The criminal liability of the athlete in the case of use of doping during sports competitions is penalized in addition to disciplinary penalties and is a means to maintain the sports norms at every competitions so that the equality between the athletes participating therein is achieved and as well ensure that no interference is unethical and internationally prohibited , The Algerian legislator has underlined the crime of doping by athletes and made it punishable for anyone who facilitates the provision of such staff in order to participate in the various sports competitions using an unnatural extra effort.
مقال
Keywords: المنشطات، المسؤولية الجزائية، المسابقات ، الرياضة ، العقوبة الجزائية .; doping , criminal liability , competitions , sport , penal punishment .